Hyundai Exodus-- exiting tradition, entering new boundaries of designing "Design a Hyundai Motors visual identity" : a written component completed in partial fulfillment of the requirements for the degree of Masters of Design at Massey University, College of Creative Arts, Auckland, New Zealand - Lee, Jae Hoon (Massey University, 2009)
This research project was conducted to fulfill a Master of design specialising in Transport Design, at Massey University’s Auckland School of Design. It was aimed to create a new visual identity for Hyundai Motors by designing a car model forecasting and utilising methods pertinent to Hyundai Motors. Simultaneously the designed car model focuses on specifically accommodating the needs of surfers. The whole philosophy behind this particular model involves three important elements of Visual Identity as pointed out by Warell; recognition, comprehension and association. As a result, in each stage of the design process, the model was designed and amended continuously to incorporate these three issues to create a design for Hyundai that targeted the surfing market. This research sets out a departure point for designing differentiated vehicle concepts for Hyundai by targeting a niche market. The Exodus was designed for a particular demographic and a subculture. The targeted market began with participants of Extreme Sports such as snowboarding, windsurfing, and surfing, but was narrowed down to surfers, because they had specific requirements that were not well catered via by existing vehicles. These requirements also translated into specific design features that allowed the development of a strongly differentiate of vehicle concept. In this way the Exodus represents an example of how specific and user needs can drive differentiated design in both a practical and visually expressive way. This process was facilitated by way of three major research stages. Firstly, a field trip to Piha, one of Auckland’s most popular surfing beaches was conducted in order to find out more about surfing culture and as a general means of vehicle observation. Secondly, informed interviews were conducted in order to gather qualitative information to generate specific user requirements and inform design development that would meet the needs of surfers. Existing car designs types were analysed to extract any design features and attributes suitable for surfers. Thirdly, a comparative analysis of two established vehicle brands, alongside Hyundai was undertaken in order to reveal the weaknesses of Hyundai’s visual identity. This phase then culminated in a research model specifically aimed at creating a new design image for them. Based on requirements developed using the above methods, the design were developed through an interactive process of sketching, modeling and critique. The aim was to create a car with an advanced design that met the functional needs of the surfing market. The main focus was to create a specific, differentiated brand image based on association, comprehension and recognition for the Hyundai.
Keywords: Hyundai Exodus; Car design; Vehicle design; Surfing; Fields of Research::290000 Engineering and Technology::290400 Automotive Engineering::290401 Automotive engineering